Carbon Dioxide Fixation and Related Properties in Sections of the Developing Green Maize Leaf - Perchorowicz, John T. (1980)
Light and dark (14)CO(2) assimilation, pulse-chase ((14)CO(2) followed by (12)CO(2)) labeling experiments both in the light and in the dark, photorespiratory activity and some enzymes (ribulose 1,5-bisphosphate (RuBP) carboxylase, phosphoenolpyruvate (PEP) carboxylase, and NADP-malic enzyme) were followed in sections of 2.5 centimeters from the base (younger tissue) to the tip (oldest tissue) of the green maize leaf. Tissue was taken from the third leaf of 12- to 16-day-old plants consisting of sections 0 to 2.5 centimeters (base), 4.5 to 7.0 centimeters (center) and 9.0 to 11.5 centimeters (top) measured from the base. Some of these properties were also determined in the intact leaves of 4-day-old maize plants. Electron microscopy indicated a Kranz anatomy in all sections. Differentiation into mesophyll granal chloroplasts and bundle sheath agranal chloroplasts had taken place only in the center and top pieces. All of the sections contained PEP carboxylase, RuBP carboxylase, and NADP-malic enzyme. The ratio of PEP:RuBP carboxylase increased from 3.03 (top) to 4.66 (base) whereas the PEP carboxylase:NADP-malic enzyme ratio rose from 2.87 (top) to 9.57 (base). Under conditions of light or dark, the majority of the newly incorporated (14)CO(2) was found in malate and aspartate in all sections and in 4-day-old leaves. The (14)C-labeling pattern typical of C(4) plants was present in the center and top sections and to a lesser extent in the 4-day-old leaves. In the base tissue, the percentage of radioactivity in malate and aspartate remained relatively constant both during photosynthesis and pulse-chase experiments. In contrast, radioactivity in glycerate-3-phosphate decreased with time coupled to an increase in sugar phosphates. To account for the isotopic pattern in the base tissue, parallel fixation by PEP carboxylase and RuBP carboxylase was proposed with the photosynthetic carbon reduction cycle functioning to some extent independently within the bundle sheath chloroplasts. The apparent lack of cooperation between the mesophyll and bundle sheath cells may have been due to inadequate levels of NADP-malic enzyme required for shuttling carbon as CO(2) from the PEP carboxylase products to the Calvin cycle.